Antiepileptic drug use in seven electronic health record databases in Europe: A methodologic comparison. Issue 5 (27th February 2014) - de Groot, Mark C. H.; Schuerch, Markus; de Vries, Frank; Hesse, Ulrik; Oliva, Belén; Gil, Miguel; Huerta, Consuelo; Requena, Gema; de Abajo, Francisco; Afonso, Ana S.; Souverein, Patrick C.; Alvarez, Yolanda; et al.
Summary: Objective: The annual prevalence of antiepileptic drug (AED) prescribing reported in the literature differs considerably among European countries due to use of different type of data sources, time periods, population distribution, and methodologic differences. This study aimed to measure prevalence of AED prescribing across seven European routine health care databases in Spain, Denmark, The Netherlands, the United Kingdom, and Germany using a standardized methodology and to investigate sources of variation. Methods: Analyses on the annual prevalence of AEDs were stratified by sex, age, and AED. Overall prevalences were standardized to the European 2008 reference population. Results: Prevalence of any AED varied from 88 per 10, 000 persons (The Netherlands) to 144 per 10, 000 in Spain and Denmark in 2001. In all databases, prevalence increased linearly: from 6% in Denmark to 15% in Spain each year since 2001. This increase could be attributed entirely to an increase in "new, " recently marketed AEDs while prevalence of AEDs that have been available since the mid‐1990s, hardly changed. AED use increased with age for both female and male patients up to the ages of 80 to 89 years old and tended to be somewhat higher in female than in male patients between the ages of 40 and 70. No differences between databases in the number of AEDs used simultaneously by a patient were found. Significance: We showed that during the study period of 2001–2009, AED prescribing increased in five European Union (EU) countries and that this increase was due entirely to the newer AEDs marketed since the 1990s. Using a standardized methodology, we showed consistent trends across databases and countries over time. Differences in age and sex distribution explained only part of the variation between countries. Therefore, remaining variation in AED use must originate from other differences in national health care systems. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here .